Terminal care at home: perspective from general practice. - Haines, A (1986)
A survey of general practitioners in north west London was undertaken by questionnaire to elicit information about problems that they had had in looking after patients at home who were terminally ill and about their perceived needs for both training and support services. The response rate was 73% (196 of 268 doctors). Thirty two per cent of respondents frequently or always had problems in controlling pain in such patients, and 45% frequently or always had difficulties in coping with the emotional distress of patients or relatives, or both. Between 20 and 30% of respondents often had problems with inadequate support services, poor communication with support services and hospital specialists, and difficulty in admitting patients who were terminally ill. Roughly half of the respondents thought that more training in managing pain and other symptoms that are associated with terminal illness would be of great help, and a similar response was noted for bereavement counselling. About 40% of respondents indicated that training in communicating with dying patients would be a great help in improving care and three quarters that more home nursing support was necessary.